2009
DOI: 10.1167/iovs.08-2646
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroups Associated with Age-Related Macular Degeneration

Abstract: AMD retinas exhibited increased mtDNA control region SNPs compared to normal retinas. This correlated with an increased frequency of mtDNA SNPs associated with haplogroups J, T and U in patients with AMD. These results implicate mitochondrial alterations in the etiology of AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 46 publications
0
85
0
Order By: Relevance
“…The C16223T variant have been described in infantile sudden death syndrome, schizophrenic patients, age-related macular degeneration, and idiopathic cardiomyopathy [28][29][30][31]. The C16294T variant is associated with Parkinson disease, infantile sudden death syndrome and age-related macular degeneration [29,30]. The T16311C variant is seen in primary prostatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C16223T variant have been described in infantile sudden death syndrome, schizophrenic patients, age-related macular degeneration, and idiopathic cardiomyopathy [28][29][30][31]. The C16294T variant is associated with Parkinson disease, infantile sudden death syndrome and age-related macular degeneration [29,30]. The T16311C variant is seen in primary prostatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Such polymorphism is also described in H, U and K haplogroups. The role of haplogroups is emphasized for various disorders such as age-related macular degeneration [30]. This mutation can increase the risk of Parkinson disease as a variation associated with haplogroup H [37].…”
Section: Discussionmentioning
confidence: 99%
“…Haplogroup H correlates with reduced risk of age-related macular degeneration, while haplogroups J and U are associated with increased risk of macular degeneration as well as increased drusen levels and retinal pigment abnormalities (Jones et al 2007;Udar et al 2009). Haplogroup H and H-nt 4336 are associated with increased risk, and haplogroups J and Uk with decreased risk, for developing PD (Shoffner et al 1993;van der Walt et al 2003;Ghezzi et al 2005;Khusnutdinova et al 2008).…”
Section: Adaptive Mtdna Variantsmentioning
confidence: 99%
“…Haplogroup H correlates with reduced risk of age-related macular degeneration, while haplogroups J and U are associated with increased risk of macular degeneration as well as increased drusen levels and retinal pigment abnormalities (Jones et al 2007;Udar et al 2009). Haplogroup H and H-nt 4336 are associated with increased risk, and haplogroups J and Uk with decreased risk, for developing PD (Shoffner et al 1993;van der Walt et al 2003;Ghezzi et al 2005;Khusnutdinova et al 2008). The haplogroup H-nt 4336 sublineage is also associated with increased AD risk, while haplogroups U and T are associated with decreased risk in certain contexts (Shoffner et al 1993;Chagnon et al 1999;Carrieri et al 2001;van der Walt et al 2004).…”
Section: Adaptive Mtdna Variantsmentioning
confidence: 99%
“…All non-African lineages belong to two founder clusters, namely haplogroups M and N; 489C, defined as haplogroup M, and 489T, defined as haplogroup N. According to the 'out of Africa' theory, these are both derived from the L3 mtDNA African lineage (30). The functional significance of the mtDNA haplogroups and their association with human behaviors requires further study, although certain haplogroups have been identified as markers for special diseases (31,32). The results from this study require validation in the form of larger population sizes and laboratory-based functional studies.…”
Section: Of Cases (Years) -------------------------------------------mentioning
confidence: 99%